Given N, count all ‘a’ and ‘b’ that satisfy the condition a^3 + b^3 = N.
Input : N = 9 Output : 2 1^3 + 2^3 = 9 2^3 + 1^3 = 9 Input : N = 28 Output : 2 1^3 + 3^3 = 28 3^3 + 1^3 = 28
Note:- (a, b) and (b, a) are to be considered as two different pairs.
Asked in : Adobe
Implementation: Travers numbers from 1 to cube root of N. a) Subtract cube of current number from N and check if their difference is a perfect cube or not. i) If perfect cube then increment count. 2- Return count.
Below is the implementation of above approach:
For n= 1, 1 pair exists For n= 2, 1 pair exists For n= 3, 0 pair exists For n= 4, 0 pair exists For n= 5, 0 pair exists For n= 6, 0 pair exists For n= 7, 0 pair exists For n= 8, 1 pair exists For n= 9, 2 pair exists For n= 10, 0 pair exists
This article is contributed by Sahil Chhabra. If you like GeeksforGeeks and would like to contribute, you can also write an article using contribute.geeksforgeeks.org or mail your article to email@example.com. See your article appearing on the GeeksforGeeks main page and help other Geeks.
Please write comments if you find anything incorrect, or you want to share more information about the topic discussed above.
- Program to count number of distinct Squares and Cubes upto N
- Count pairs with Odd XOR
- Count pairs with given sum | Set 2
- Count pairs (i,j) such that (i+j) is divisible by A and B both
- Count of pairs (x, y) in an array such that x < y
- Count of pairs from 1 to a and 1 to b whose sum is divisible by N
- Count number of pairs (A <= N, B <= N) such that gcd (A , B) is B
- Count pairs (a, b) whose sum of squares is N (a^2 + b^2 = N)
- Count Pairs from two arrays with even sum
- Count of pairs of (i, j) such that ((n % i) % j) % n is maximized
- Count pairs in an array such that frequency of one is at least value of other
- Count pairs from two arrays having sum equal to K
- Count pairs with sum as a prime number and less than n
- Count ordered pairs with product less than N
- Count pairs (A, B) such that A has X and B has Y number of set bits and A+B = C